STRATEGI EUFEMISME DAN DISFEMISME DALAM PEMBERITAAN POLEMIK MAKAN BERGIZI GRATIS PADA DETIK.COM DAN CNN INDONESIA - Suryana, Agus; Munandar, Jajang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe euphemism and dysphemism strategies in online news coverage of the polemic surrounding the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) on Detik.com and CNN Indonesia. The study is grounded in the view that media language is not neutral because news texts select, emphasize, and interpret social reality through particular frames (Entman, 1993; Sulehry & Wallace, 2021). This research applies a descriptive qualitative method within a critical discourse analysis perspective. The data consist of words, phrases, clauses, and sentences containing euphemistic and dysphemistic indications in Detik.com and CNN Indonesia news reports on MBG, particularly regarding menu quality, milk replacement, zakat funding, program evaluation, and food poisoning cases. The analysis was conducted through identification, classification, functional interpretation, and cross-media comparison. The findings show that euphemism is used to soften technical, administrative, and policy-related problems, as reflected in expressions such as replaced, fulfilling nutritional needs, beneficiaries, evaluation, shortcomings, and mechanism adjustment. Conversely, dysphemism is used to sharpen criticism, emphasize risk, and construct urgency, as seen in expressions such as poisoning, endangering children, full of conflicts of interest, deviating, danger, and cannot be taken lightly. Detik.com tends to present conflict through source quotations and field-experience descriptions, whereas CNN Indonesia foregrounds evaluative diction within the frames of risk, accountability, and policy urgency. These findings indicate that euphemism and dysphemism function as discourse strategies that shape public perception of the MBG policy.